"Injury, illness, and work restriction in merchant seafarers". Issue 6 (4th May 2015) - Lefkowitz, Rafael Y.; Slade, Martin D.; Redlich, Carrie A.
<x xml:space="preserve">Abstract</x> Background Research on seafarer medical conditions at sea is limited. This study describes the frequency and distribution of seafarer injury and illness at sea, and explores potential risk factors for resultant lost work. Materials and Methods The study analyzed a telemedicine database of 3, 921 seafarer medical cases between 2008 and 2011 using descriptive statistics and logistic regression. Results There were over twice as many illness cases (n = 2, 764, 70.5%) as injury (n = 1, 157, 29.5%) cases. Disability was more often secondary to illness (n = 646, 54.3%), predominantly from gastrointestinal, dermatologic, and respiratory conditions. Logistic regression revealed age, rank, and worksite as potential risk factors for lost work. Conclusions This study emphasizes illness as a significant problem occurring in seafarers at sea. Future research should further elucidate risk factors for illness, as well as injury, to inform preventive measures and reduce seafarer disability. Am. J. Ind. Med. 58:688–696, 2015. © 2015 Wiley Periodicals, Inc.